Peran Ukuran Bank Memoderasi Kecukupan Modal dan Konsentrasi Kepemilikan Terhadap Kinerja Keuangan Bank - Rachmat Indradi; Taswan Taswan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The banking sector is the backbone of the Indonesian economy and has a very important role as a financial intermediary. The purpose of this study is to analyze and explain the effect of capital adequacy on banking performance, the effect of ownership concentration on banking performance, the effect of firm size concentration on banking performance, the role of firm size moderating capital adequacy on banking performance, the role of firm size moderating ownership concentration on banking performance. banking performance. The population used in this study were banking companies listed on the Indonesia Stock Exchange (IDX) during the study period (December 2015 – December 2020). In carrying out this research, the data used are secondary data in the form of historical reports of financial ratios of each banking company listed on the Indonesia Stock Exchange and financial statements in the form of quarterly financial statements of banking companies listed on the IDX which have been published in the period research and record. The results of the analysis are banking performance as proxied by return on assets (ROA) will increase if the CAR variables, ownership concentration and company size do not change (fixed), CAR has a significant positive effect on banking performance (ROA), ownership concentration has no effect on banking performance (ROA), banking size has a significant positive effect on banking performance (ROA), banking size strengthens the relationship between CAR and banking performance (ROA), banking size has no effect on the relationship between ownership concentration and banking performance (ROA).